Online Antenatal Care During the COVID-19 Pandemic: Opportunities and Challenges - Wu, Huailiang; Sun, Weiwei; Huang, Xinyu; Yu, Shinning; Wang, Hao; Bi, Xiaoyu; Sheng, Jie; Chen, Sihan; Akinwunmi, Babatunde; Zhang, Casper J P; Ming, Wai-Kit (Journal of medical Internet research, 2020)
People across the world have been greatly affected by the ongoing coronavirus disease (COVID-19) pandemic. The high infection risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in hospitals is particularly problematic for recently delivered mothers and currently pregnant women who require professional antenatal care. Online antenatal care would be a preferable alternative for these women since it can provide pregnancy-related information and remote clinic consultations. In addition, online antenatal care may help to provide relatively economical medical services and diminish health care inequality due to its convenience and cost-effectiveness, especially in developing countries or regions. However, some pregnant women will doubt the reliability of such online information. Therefore, it is important to ensure the quality and safety of online services and establish a stable, mutual trust between the pregnant women, the obstetric care providers and the technology vis-a-vis the online programs. Here, we report how the COVID-19 pandemic brings not only opportunities for the development and popularization of online antenatal care programs but also challenges.